Co-delivery of doxorubicin and recombinant plasmid pHSP70-Plk1-shRNA by bacterial magnetosomes for osteosarcoma therapy - Cheng L (Dove Medical Press, 2016)
Li Cheng, Youqun Ke, Shuisheng Yu, Juehua Jing Department of Orthopaedics, The Second Affiliated Hospital of Anhui Medical University, Anhui Medical University, Hefei, Anhui, People’s Republic of China Abstract: To explore a novel combination of chemotherapy, gene therapy, and thermotherapy for osteosarcoma, a targeted heat-sensitive co-delivery system based on bacterial magnetosomes (BMs) was developed. The optimal culture conditions of magnetotactic bacteria (MTB) AMB-1 and characterization of BMs were achieved. A recombinant eukaryotic plasmid heat shock protein 70-polo-like kinase 1-short hairpin RNA (pHSP70-Plk1-shRNA) under transcriptional control of a thermosensitive promoter (human HSP70 promoter) was constructed for gene therapy. Doxorubicin (DOX) and pHSP70-Plk1-shRNA were included in the targeted thermosensitive co-delivery system, and in vitro DOX release activity, targeted gene silencing efficiency and in vitro antitumor efficacy were investigated. The results showed that the optimal culture conditions of MTB AMB-1 are an oxygen concentration of 4.0%, a pH value of 7.0, 20 µmol/L of ferrous sulfate, 800 mg/L of sodium nitrate, and 200 mg/L of succinic acid. The temperature of BMs reached 43°C within 3 minutes and could be maintained for 30 minutes by adjusting the magnitude of the alternating magnetic field (AMF). The diameters of BMs, BM-DOX, BM-recombinant eukaryotic plasmid pHSP70-Plk1-shRNA (shPlk1), and BM-DOX-shPlk1 were 43.7±4.6, 79.2±5.4, 88.9±7.8, and 133.5±11.4 nm, respectively. The zeta potentials of BMs, BM-DOX, BM-shPlk1, and BM-DOX-shPlk1 were -29.4±6.9, -9.5±5.6, -16.7±4.8, and -10.3±3.1 mV, respectively. Besides, the system exhibited good release behavior. DOX release rate from BM-DOX-shPlk1 was 54% after incubation with phosphate-buffered saline at 43°C and 37% after incubation with 50% fetal bovine serum, which was significantly higher than that at 37°C (P<0.05). In addition, the expressions of Plk1 mRNA and protein were significantly suppressed in cells treated with BM-DOX-shPlk1 following hyperthermia treatment under the influence of an AMF compared to other groups (P<0.05). Furthermore, evaluation of the effect of in vitro antitumor revealed that BM-DOX-shPlk1 following hyperthermia treatment under the influence of an AMF was significantly more effective than others in tumor inhibition. In conclusion, the new heat-sensitive co-delivery system represents a promising approach for the treatment of cancer. Keywords: magnetotactic bacteria, heat-inducible gene expression, alternating magnetic field, chemotherapy, gene therapy, thermotherapy